2014
DOI: 10.1037/a0035032
|View full text |Cite
|
Sign up to set email alerts
|

Conflict-triggered top-down control: Default mode, last resort, or no such thing?

Abstract: The conflict monitoring account posits that globally high levels of conflict trigger engagement of top-down control; however, recent findings point to the mercurial nature of top-down control in high conflict contexts. The current study examined the potential moderating effect of associative learning on conflict-triggered top-down control engagement by testing the Associations as Antagonists to Top-Down Control (AATC) hypothesis. In 4 experiments, list-wide proportion congruence was manipulated, and conflict-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
352
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(401 citation statements)
references
References 68 publications
40
352
9
Order By: Relevance
“…Other than those reported, no other main effects or interactions were significant in this or the subsequent experiment. Following prior studies that had employed the design used here (though without the precue manipulation; Bugg, 2014;cf. Blais & Bunge, 2010;Bugg et al, 2008), we conducted separate ANOVAs for the PC75/PC25 items and the PC50 items.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other than those reported, no other main effects or interactions were significant in this or the subsequent experiment. Following prior studies that had employed the design used here (though without the precue manipulation; Bugg, 2014;cf. Blais & Bunge, 2010;Bugg et al, 2008), we conducted separate ANOVAs for the PC75/PC25 items and the PC50 items.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent research has demonstrated, however, that this conclusion may be specific to list-based PC designs that use small sets (comprising two words and colors) of stimuli to establish the overall PC of the list (i.e., via 75 %-and 25 %-congruent items; Bugg, 2014;Bugg & Chanani, 2011;cf. Bugg, McDaniel, Scullin, & Braver, 2011;Hutchison, 2011).…”
Section: Interactivity Of Proactive and Reactive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In many reports, the PC effect did not transfer to diagnostic items (e.g., Blais & Bunge, 2010;Bugg, Jacoby, & Toth, 2008). However, in some conditions a LLPC effect is observed (e.g., Bugg, 2014;Bugg, McDaniel, Scullin, & Braver, 2011;Hutchison, 2011;Wühr, Duthoo, & Notebaert, 2015).…”
Section: Now Consider the Proportion Congruent (Pc) Effectmentioning
confidence: 99%
“…Specifically, distracting words accurately predict the correct response on congruent trials in the mostly congruent condition, and (in many task variants) accurately predict a specific incongruent response in the mostly incongruent condition (e.g., if "red" is presented most often in yellow). Considerable debate has focussed on whether contingency learning provides a sufficient account of the PC effect, or whether conflict adaptation must also be assumed (e.g., Abrahamse, Duthoo, Notebaert, & Risko, 2013;Atalay & Misirlisoy, 2012, 2014Bugg, 2014Bugg, , 2015Bugg & Hutchison, 2013;Bugg, Jacoby, & Chanani, 2011;Grandjean et al, 2013;Hazeltine & Mordkoff, 2014;Levin & Tzelgov, 2016;Schmidt, 2013aSchmidt, , 2014a.…”
Section: Now Consider the Proportion Congruent (Pc) Effectmentioning
confidence: 99%